Study on the Influencing Factors of College Students Using AIGC to Assist Studies Behavior - Ma, Yuqing (International Journal of Computer Science and Information Technology, 2024)
This study explores the influencing factors of college students’ use of AIGC to assist studies behavior, builds a new model which combines TAM model and TPB theory, and adds the factor of trust into the model. At the same time, it explores differences of the use of AIGC to assist studies behavior of liberal arts students and science students. Data were collected by distributing questionnaires online and spreading questionnaires on social platforms, and a total of 418 valid questionnaires were collected. Regression analysis shows that the use of AIGC is influenced by five factors. Among the influencing factors, liberal arts students are more significantly affected by subjective norms and trust, while science students are more significantly affected by perceived behavior control.